Downregulation of metabotropic glutamate receptor 5 inhibits hepatoma development in a neurotoxin rotenone-induced Parkinson's disease model. (15th May 2018) - Bai, Xiao Xu; Gu, Li; Yang, Hui Min; Xi, Shao Song; Xia, Ning; Zhang, Song; Zhang, Hong
Graphical abstract: Highlights: Rotenone-induced neuron injury inhibits hepatoma cell growth, migration, invasion, and promotes apoptosis. Both reduced mGlu5 expression and its activity have effects on hepatoma cells. MGlu5 mediated ROS/JNK signaling pathways enhance the apoptosis of hepatoma cells promoted by rotenone-induced neuron injury. Downregulation of mGlu5 inhibits hepatoma development in a rotenone-induced animal model of PD. Abstract: Clinical epidemiological studies have shown that there is a link between Parkinson's disease (PD) and cancer, but how PD regulates cancer development remains unknown. In our study, the effect of metabotropic glutamate receptor 5 (mGlu5 ) on hepatoma was explored in a rotenone-induced PD model both in vitro and in vivo. We found that conditioned media derived from MN9D dopaminergic neuronal cells by rotenone-induced toxicity inhibited the growth, migration, invasion and promoted apoptosis of Hepa1-6 cells, which corresponded with decreased expression of mGlu5 . Furthermore, treatment with 2-methyl-6-(phenylethynyl)pyridine (MPEP), a mGlu5 antagonist and knockdown of mGlu5, further reduced ATP levels and migration distance, and increased cleavage of caspase-3 in Hepa1-6 cells. Additionally, we found that conditioned media derived from rotenone-treated MN9D dopaminergic neuronal cells enhanced reactive oxygen species (ROS) generation and JNK phosphorylation, which could be further increased by MPEP treatment, and attenuated by mGlu5 agonist, (RS)-2-Chloro-5-hydroxyphenylglycine (CHPG) and ROS scavenger, N-acetyl-l -cysteine (NAC). The results indicated that down-regulation of mGlu5 promoted cell apoptosis through the intracellular ROS/JNK signaling pathway in a rotenone-induced cellular PD model. These findings were confirmed in vivo in a rotenone-induced rat model of PD combined with diethylnitrosamine (DEN)-induced hepatoma. Expression of Ki67 was decreased, and the levels of caspase-3 and p-JNK were increased in this model, which was accompanied by a decrease in protein expression of mGlu5 . The study suggest that negative regulation of mGlu5 may inhibit hepatoma development in a rotenone-induced PD model, and as such may help with our further understanding of the correlation between PD and cancer.